Thermoelectric Transport from First-Principles : Biphenyl-Based Single-Molecule Junctions - Bürkle, Marius; Pauly, Fabian; Asai, Yoshihiro (My University, 2016)
Using first-principles electronic structure methods in conjunction with nonequilibrium Green function (NEGF) techniques, we study the thermoelectric transport through biphenyl-based single-molecule junctions. We show, based on our recently published works and their present extension to include also the electron energy current, that the single-molecule conductance, junction thermopower, and electron thermal conductance strongly depend on the choice of the molecular anchor group and on the geometry of the investigated gold-biphenyl-gold contacts. We compare two different anchor groups, sulfur and cyano. The electron-donating S anchor group gives rise to a positive thermopower, while the electron-withdrawing cyano anchor results in a negative thermopower. For the S-terminated biphenyl a strong variation of the transport coefficients with respect to the binding motif is observed, for CN-terminated biphenyl such variations remain small.
Keywords: 530